Postharvest quality of yellow passion fruit grown using espalier and trellis systems in an annual growth cycle (Acta Scientiarum. Agronomy, 2025)
Yellow passion fruit (Passiflora edulis) is a vine plant whose pulp is mainly used for juice production. Brazil accounts for approximately 90% of global passion fruit production, while Europe is an emerging market. Passion fruit cultivation requires support structures, typically oriented vertically using the espalier system or horizontally using the trellis system, constituting up to 70% of production costs. Despite its native origin, there is limited research on the impact of cultivation systems on fruit quality. This study compares trellis systems with two wires to the espalier system across two growing seasons under annual cultivation. Fruits were harvested when at least two-thirds of the skin turned yellow. Rainfall accumulation and light availability within each system were measured. Various fruit characteristics-including skin color, skin thickness, fruit mass, longitudinal and transverse diameters, pulp mass, pulp yield with seeds, total soluble solids, titratable acidity, and ascorbic acid content—were evaluated in both systems across both seasons. Results indicate that the trellis system consistently produced higher pulp mass and larger fruit diameter across seasons. No significant differences were found in postharvest quality between the systems. Based on these findings, the trellis system is recommended for annual yellow passion fruit cultivation.